2016
DOI: 10.3171/2014.12.jns141308
|View full text |Cite
|
Sign up to set email alerts
|

Volume-staged radiosurgery for large arteriovenous malformations: an evolving paradigm

Abstract: abbreviatioNs ARE = adverse radiation effect; AVM = arteriovenous malformation; CI = confidence interval; CTCAE V4.0 = Common Terminology Criteria for Adverse Events version 4.0; HR = hazard ratio; mRBAS = modified radiosurgery-based AVM score; SM = Spetzler-Martin; SRS = stereotactic radiosurgery; VRAS = Virginia Radiosurgery AVM Scale; VS = volume staged. submitted July 17, 2014. accepted December 9, 2014. iNclude wheN citiNg Published online July 3, 2015; DOI: 10.3171/2014.12.JNS141308. disclosure The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 47 publications
3
41
1
Order By: Relevance
“…19 A few studies have shown promising results in terms of obliteration rates and adverse events following volume-staged SRS for large cerebral AVMs. Our obliteration rate of 42% is in line with results previously reported by others, 2,3,6,11,13,23,26,27 which range from 10% to 62% for series describing more than 10 patients. A significant proportion of our patients had a nidus characterized by diffuse morphology and features of perinidal angiogenesis and high nidal flow; these features are associated with a lower rate of postradiosurgical obliteration.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…19 A few studies have shown promising results in terms of obliteration rates and adverse events following volume-staged SRS for large cerebral AVMs. Our obliteration rate of 42% is in line with results previously reported by others, 2,3,6,11,13,23,26,27 which range from 10% to 62% for series describing more than 10 patients. A significant proportion of our patients had a nidus characterized by diffuse morphology and features of perinidal angiogenesis and high nidal flow; these features are associated with a lower rate of postradiosurgical obliteration.…”
Section: Discussionsupporting
confidence: 92%
“…Many options are theoretically available within the armamentarium of the treating neurosurgeon. Resection of an AVM previously reduced by GKRS can be an effective option, as reported by Seymour et al 26 Repeating a radiosurgical procedure can also be an effective option, so long as it is technically feasible according to the previously irradiated volumes and dosimetry plan, and adverse event risks are carefully weighed.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Volume-staged radiosurgery [7,8,9]: In this approach, the AVM is divided into several regions (typically 2–4). Each region is treated separately with a high single fraction dose.…”
Section: Introductionmentioning
confidence: 99%